Notre-Dame-du-Travail (Paris), une église au tournant du XIXe siècle et du XXe siècle - Cécile Dupré (In Situ)
Notre-Dame-du-Travail’s church (Our Lady of Labour) is located in the XIVth district of Paris. It epitomizes many characteristics of the few churches built at the turn of the XXth century: its innovative architecture reveals a vast visible iron frame, and a décor closely bound with the architecture. Between October and December 2007 the church was surveyed. It provided the opportunity to explore the limits of survey and clarified a page of the history of social Catholicism.